2020
DOI: 10.1002/14651858.cd007892.pub7
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal preparation with antiseptic solution before cesarean section for preventing postoperative infections

Abstract: Vaginal preparation with antiseptic solution before cesarean section for preventing postoperative infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 45 publications
2
39
1
Order By: Relevance
“…12,13 However, those studies are outdated due to the emerging new evidence such as vaginal cleansing and preoperative intravenous azithromycin. 4,5,14 A secondary analysis of a randomized controlled trial found that women who had 4 evidence-based interventions (preoperative cefazolin prior to skin incision, chlorhexidine-alcohol skin antisepsis, closure of subcutaneous layer, and suture subcuticular skin closure) compared to those who did not have all 4 interventions had 67% lower odds of surgical site infections. 12 However, the randomized controlled trial was conducted for a different purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 However, those studies are outdated due to the emerging new evidence such as vaginal cleansing and preoperative intravenous azithromycin. 4,5,14 A secondary analysis of a randomized controlled trial found that women who had 4 evidence-based interventions (preoperative cefazolin prior to skin incision, chlorhexidine-alcohol skin antisepsis, closure of subcutaneous layer, and suture subcuticular skin closure) compared to those who did not have all 4 interventions had 67% lower odds of surgical site infections. 12 However, the randomized controlled trial was conducted for a different purpose.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13] Further, newer evidence has made methods and results of previous studies obsolete. 4,14 The Accreditation Council for Graduate Medical Education (ACGME) implemented a requirement within all graduate medical education curricula for residents to perform patient safety and quality improvement projects. 15 Encouraged by this requirement, a residentdriven quality initiative using an evidence-based surgical bundle for cesarean delivery was implemented in December 2016 at MedStar Washington Hospital Center.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review in 2018 concluded that vaginal preparation with povidone-iodine or chlorhexidine solution immediately before caesarean delivery probably reduces the rates of postoperative endometritis. 8 It was also recommended in a systematic review and meta-analysis of best practice perioperative strategies for preventing caesarean section SSIs published in the BJOG . 7 Vaginal preparation with povidone-iodine immediately before caesarean section is recommended by the WHO.…”
Section: Introductionmentioning
confidence: 99%
“…Patient safety process adherence rate: Rate of six indicators: use of pulse oximetry at the time of initiation of anaesthesia; administration of prophylactic antibiotics within 60 min before incision; oral confirmation, immediately before incision, of the identity of the patient, operative site and procedure to be performed; completion of an instrument, sponge and needle count at the end of the procedure; appropriate operative site cleansing (skin preparation with Chlorhexidine-alcohol or iodine-based solution); and vaginal preparation with povidone-iodine 2 13 34 64 65…”
mentioning
confidence: 99%